Higher Education, Employment Opportunities and Women Empowerment in Pakistan: Nasim Khan Mahsud, Rabia Ali (PJDOL, 2023)
This article draws from a PhD study to explore potential relationship among higher education, employment opportunities (being indicators of globalization) and women empowerment in Pakistan. It precisely focuses on women’s status, individual autonomy, family inter-personal relationships, and economic empowerment. The study was conducted by using the sequential, mix-method design. Initially data from 376 women were collected through survey followed by 26 in-depth interviews. The current paper is based on qualitative data acquired from 26 respondents from three-03 different domains of expertise (Parliamentarians, Journalists, andhigh-profile academicians/deans, vice-chancellors).